Calcium intake and hypertension in pregnancy - Nurhidayati, Rachmi; Widyasih, Hesty; Margono, Margono (Poltekkes Kemenkes Yogyakarta, 2018)
Hypertension in pregnancy is still one of the causes of maternal death in Indonesia. In 2016, the maternal mortality rate in Special Region of Yogyakarta had increased. The most cases of maternal mortality in Bantul Regency which is caused by complication of hypertension in pregnancy by 33%. Meanwhile, the majority of pregnant women in Indonesia have an average calcium intake that is classified as less, which is 649.9 mg/day. The aim of this study was to the correlation of calcium intake with hypertension in pregnancy in Bantul Community Health Center in 2018, the type of analytical survey research with cross-sectional design was conducted. The population of this study was pregnant women in the third trimester in Bantul Regency Community Health Center in 2018 with a sample size of 95. The sampling technique used was consecutive sampling. The data analysis used chi-square test. Calcium intake in pregnant women in Bantul Regency Community Health Center in 2018 is classified as inadequate at 90.5%. Pregnant women with less calcium intake who experienced hypertension in pregnancy were as much as 5.8%, while pregnant women with adequate calcium intake who experienced hypertension in pregnancy were as much as 11.1%. Based on the chi-square test known p-value = 0.639. There was no significant correlation between calcium intake with hypertension in pregnancy at Bantul Regency Community Health Center in 2018.